Evaluasi Efektivitas Pelatihan Peningkatan Kapasitas di MI Hidayatun Najah Dengan Model Kirkpatrick - Rustyawati, Dian; Fauzi, M (Transformation of Islamic Management and Education, 2025)
This study focuses on evaluating the effectiveness of teacher and educational personnel training at MI Hidayatun Najah Tuban using the Kirkpatrick evaluation model, which consists of four levels: reaction, learning, behaviour, and results. The main objective of the research is to examine the extent to which the training programme improves participants’ perceptions, learning outcomes, workplace behaviour, and organisational performance. The study employed a quantitative research design grounded in a positivist approach. The research population comprised all teachers and educational staff who participated in the training programme, totalling 82 individuals, and a saturated sampling technique was applied. Data were collected through questionnaires, observation, and pre-test and post-test instruments, and analysed using Likert scale analysis, descriptive statistics, and paired sample t-tests with the support of Microsoft Excel and SPSS 25.0. The findings indicate that, at the reaction level, participants showed very positive responses to the training materials, delivery methods, and relevance to their professional needs. At the learning level, statistical analysis revealed a significant increase in participants’ knowledge and understanding, as evidenced by the substantial difference between pre-test and post-test scores. Behavioural evaluation results demonstrate that participants were able to transfer learning into practice, reflected in increased enthusiasm, collaboration, and improved job performance. At the results level, the training programme produced significant organisational impacts, particularly in enhancing the quality of educational services provided by the institution. The implications of this study suggest that the Kirkpatrick model is an effective and relevant framework for evaluating training in Islamic educational institutions. The results underscore the importance of systematic training and continuous evaluation to strengthen human resource development and institutional performance.